Koordinasi Antar Instansi Dalam Pelaksanaan Program Rehabilitasi Sosial Rumah Tidak Layak Huni Kota Surabaya - Yuananta; Sri Umiyati (Policy and Maritime Review, 2023)
Social rehabilitation of uninhabitable houses is a construction program for uninhabitable houses that need community participation. The construction program of social rehabilitation for the uninhabitable house is conducted by Social services in Surabaya and the Poor family Development unit. The study aims to describe and analyze institution coordination in the implementation of construction programs for uninhabitable houses. The theoretical framework uses coordination theory in Inu Kencana (2011) i.e. arrangement, synchronization, common interest, and common goals. This is a qualitative descriptive method and population sampling techniques are applied through observation, interview, and documentation. The results indicate that the indicators of arrangement, synchronization, and common goals are well applied in the implementation of social rehabilitation of the uninhabitable house program in North Perak. Whereas, the indicator of common interest is not well applied. For this reason, the program should be evaluated regarding the disbursement of funds in the implementation of social rehabilitation of uninhabitable houses.